Effect Of Compensation, Environment and Leadership Style On Employee Spirit and Performance Through Motivation - Yani, Muhammad (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the effect of compensation, environment and leadership style on employee morale and performance through study motivation at PT. EX. This study used a sample of 95 respondents, namely employees of the production section of PT. EX. which is taken using non-probability sampling techniques from the population or production employees. The data analysis technique used the Structural Equation Modeling (SEM) Partial Least Square (PLS) approach using the Smart PLS version 3.0 software. The results showed that: Compensation and work environment have a positive and significant effect on work motivation, compensation and work environment have a positive and significant effect on morale, work motivation has a positive and significant effect on employee performance and employee morale. Leadership style has no effect on work motivation, employee performance and morale. Compensation and work environment have no effect on employee performance. Compensation has a positive and significant effect on employee performance through work motivation, work environment has a positive and significant effect on employee performance through work motivation, compensation has a positive and significant effect on work motivation through work motivation, the environment has a positive and significant effect on morale through work motivation. In addition, motivation cannot mediate the relationship between leadership style and employee performance, and motivation cannot mediate the relationship between leadership style and morale.